FAMILY DIET AND STUNTING RISK - Lina, Helina Himmatul Ulya (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
This study aims to investigate family diet and stunting risk, the role of parents in creating children's nutritional health, referring to the global context showing that stunting is still a serious child health problem, with significant long-term impacts. The main focus of this study includes understanding the family diet applied by parents in fulfilling children's nutrition, exploring the role of parents in choosing and compiling daily food menus that support children's nutritional needs, and identifying factors that affect family diets in Ceria Blora Kindergarten. This study uses a qualitative approach with a case study method. Data were obtained through in-depth interviews with parents and teachers, direct observation, and documentation analysis. Data analysis techniques include data collection, data reduction, data presentation, and conclusion drawn. The validity of the data is maintained by using source and method triangulation techniques. This research is expected to provide a better understanding of the family diet applied by parents in fulfilling children's nutrition, the role of parents in choosing and compiling daily food menus that support children's nutritional needs, factors that affect family diets in Ceria Blora Kindergarten. This research is expected to be a reference in developing nutrition education programs for parents to prevent the risk of stunting among early childhood